Effectiveness of text messaging interventions for the management of depression: A systematic review and meta-analysis. (October 2019) - Senanayake, Buddhika; Wickramasinghe, Sumudu I; Chatfield, Mark D; Hansen, Julie; Edirippulige, Sisira; Smith, Anthony C
Introduction: Depression is a leading cause of human disability. Telemedicine-based interventions using text messaging are currently being trialled for the management of community-based clients with clinical depression. However, little is known about the effectiveness of such methods. Methods: We searched the databases PubMed, Embase, Informit, Cochrane Central Register of Controlled Trials, PsycINFO and Scopus for randomised controlled trials (RCTs) published between January 2000 and April 2019. Studies comparing text messaging interventions to a comparator group for patients with depression were included in the review. Articles were assessed for quality using the Joanna Briggs Institute critical appraisal checklist for RCTs. Results: Nine RCTs (945 patients: 764 adults and 181 adolescents) were included in the systematic review. Five studies used text messaging as the only intervention, whilst the remaining combined text messaging with other treatment modalities such as behavioural activation or cognitive behavioural therapy. A meta-analysis was conducted on seven selected RCTs (845 patients: 664 adults and 181 adolescents). The standardised mean reduction in depression due to text messaging interventions was 0.23 (95% confidence interval: –0.02 to 0.48). There was evidence of heterogeneity in treatment effect between studies. Discussion: There is marginal evidence supporting text messaging interventions as an effective treatment modality for people living with clinical depression. However, further research is needed to determine how best to utilise text-message interventions alongside other conventional forms of health services delivery.